2016
DOI: 10.1292/jvms.15-0378
|View full text |Cite
|
Sign up to set email alerts
|

Partial costectomy for tracheal collapse and stenosis associated with perinatal rib fracture in three Japanese Black calves

Abstract: 2.3-month-old (Case 1), one-month-old (Case 2) and 6-month-old (Case 3), Japanese Black calves presented with mild to severe wheezing. All calves had histories of dystocia at birth with breech presentation. Physical examination, thoracic radiography, endoscopy or computed tomography indicated wheezing associated with tracheal collapse and stenosis caused by perinatal rib fractures. Partial resection of the fractured first and second ribs was performed on all calves. The respiration in Cases 1 and 2 immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 11 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…In case 1, the fractured first left rib had displaced the tracheal stenosis; thus, wheezing was considered to be due to the physical compression of the trachea. 8 The cranial thorax can be difficult to depict on a standing radiograph because the cranial thorax is superimposed with the scapula/humerus; however, CT images are cross-sectional, allowing the cranial thorax to be observed easily. 9 Furthermore, cracks with no bony callus were identified in the left ninth, tenth and eleventh ribs.…”
Section: Discussionmentioning
confidence: 99%
“…In case 1, the fractured first left rib had displaced the tracheal stenosis; thus, wheezing was considered to be due to the physical compression of the trachea. 8 The cranial thorax can be difficult to depict on a standing radiograph because the cranial thorax is superimposed with the scapula/humerus; however, CT images are cross-sectional, allowing the cranial thorax to be observed easily. 9 Furthermore, cracks with no bony callus were identified in the left ninth, tenth and eleventh ribs.…”
Section: Discussionmentioning
confidence: 99%
“…Rib fractured neonates, not necessarily with tracheal stenosis, tended to present with dyspnea at a later stage. Cranial rib fractures including at the 1st or 2nd rib and subsequent tracheal stenosis have been well reported in calves ( Fingland et al., 1990 ; Hidaka et al., 2016 ; Jelinski & Vanderkop, 1990 ). Four out of five scanned or necropsied calves (Calf 1, 4, 10, and 13), however, presented with pneumonia at the sites of rib fractures in this study, despite four calves not having tracheal stenosis; this clearly indicates that perinatal rib fractures trigger respiratory disease other than tracheal stenosis at later stages after birth.…”
Section: Discussionmentioning
confidence: 99%
“…These potential economic losses through conservative treatment imply the importance of surgery for rib fractures. Partial costectomy to treat fractured ribs was reported to improve respiration after surgery in all the three calves with tracheal collapse and stenosis at 1 to 6 months old ( Hidaka et al., 2016 ). This operation may be adapted to rib fractured calves with pneumonia, although proficient operators, surgical facilities that can anaesthetize with isoflurane, and careful nursing are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery with prosthesis procedure has provided low success rate (approximately 30%) and the method will require prosthetic material removal after growth of the patient [2,3,10]. Authors and Fujikawa et al reported that partial costectomy led to improvement in the clinical condition of the calves and indicated its availability [4,5]. In these previous reports, unfortunately, criteria for surgical intervention has yet not been discussed in calves with the disease.…”
mentioning
confidence: 99%